2001
DOI: 10.1152/ajpheart.2001.280.2.h528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ascorbic acid treatment on conduit vessel endothelial dysfunction in patients with hypertension

Abstract: Hypertension is associated with low plasma ascorbic acid levels and impaired endothelial function. Recent evidence suggests that increased vascular oxidative stress contributes to the pathophysiology of endothelial dysfunction and hypertension. We recently showed that chronic oral ascorbic acid therapy lowers blood pressure in hypertensive patients. We hypothesized that it would also improve endothelial vasomotor function. In a randomized, double-blind, placebo-controlled study, we examined the effect of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 46 publications
3
72
1
Order By: Relevance
“…Importantly, there was no improvement in forearm vascular responses to the endothelium-independent vasodilator sodium nitroprusside, which suggests that the beneficial effects of fruit and vegetable intake are related to protective effects on the endothelium 156 . The data from this study are in contrast to forearm plethysmography studies that assessed the effect of ascorbic acid on forearm vascular responses and suggest that a balanced, pragmatic approach that considers whole food and dietary patterns may be the best means of improving the overall vascular phenotype of patients with hypertension 156,[178][179][180] . Increased fruit and vegetable consumption may also make patients more likely to adopt other favourable dietary modifications, such as reduced salt and fat consumption.…”
mentioning
confidence: 59%
“…Importantly, there was no improvement in forearm vascular responses to the endothelium-independent vasodilator sodium nitroprusside, which suggests that the beneficial effects of fruit and vegetable intake are related to protective effects on the endothelium 156 . The data from this study are in contrast to forearm plethysmography studies that assessed the effect of ascorbic acid on forearm vascular responses and suggest that a balanced, pragmatic approach that considers whole food and dietary patterns may be the best means of improving the overall vascular phenotype of patients with hypertension 156,[178][179][180] . Increased fruit and vegetable consumption may also make patients more likely to adopt other favourable dietary modifications, such as reduced salt and fat consumption.…”
mentioning
confidence: 59%
“…[21][22][23] It is still unclear whether oxidative stress causes hypertension in humans and only a few small clinical studies showed a blood pressure-lowering effect of anti-oxidants, [24][25][26] with most large antioxidant clinical trials failing to demonstrate any cardiovascular benefit and blood pressure lowering. [27][28][29] Nevertheless, what is evident is that oxidative stress has a critical role in the molecular mechanisms associated with cardiovascular and renal injury in hypertension and that hypertension itself can contribute to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen trials [8][9][10][11][12][13][14][15][16][17][18][19][20] making up 14 separate group populations were identified and analyzed providing a total pooled population of 284 hypertensive patients (52% female), with a weighted mean age of 58.8 ± 9.5 years and a weighted mean body mass index of 28.5 ± 1.9 Kg/m 2 . Median vitamin C dose and study intervention duration was 500mg/day and 6 weeks respectively ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials performed to assess the effect of vitamin C supplementation on blood pressure in hypertensive individuals have met with mixed results. [8][9][10][11][12][13][14][15][16][17][18][19][20] In 1997 Ness et al concluded that there were too few clinical trials, and those reported at that time were generally too small and too varied to provide confirmatory evidence for a casual relationship. 21 This study was undertaken in order to evaluate the current clinical evidence that vitamin C supplementation lowers both systolic and diastolic blood pressure in hypertensive individuals, and to also review the hypothesized mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%